Changing the Function of Residential Space to Trade in Terms of The Occupant Aspect (Case Study Kambang Iwak Area Palembang City) - Lestari, Endang Sri (International Conference on Multidisciplinary Research, 2020)
Increasing population growth in urban areas is generally accompanied by increasingly narrow job opportunities, causing many urban residents to carry out activities in the informal sectors, such asÂ  small-scale trading activities. These activities are generally carried out by most residents living on theside of the main road. More than 50% of the residentsâ€™ houses on Jalan Merdeka Street of Kambang Iwak Palembang have changed their function to a commercial building; thus, it is necessary to conduct research on the trade public space that grows in the area. This research is field research that collectedvisual data and interviews with related parties. Research showed that the emergence of commercial public space in housing is caused by the proximity of the house and the relationship between the house and road space. The trading space functions as a public space, forming attributes in the form of accessibility, visibility, sociality, and adaptability. Commercial public spaces take place in the house and yard because they have proximity, visuality, adaptation, and activity related to public spaces. Keywords: Residential Space Function, Side of the Main Road, Merdeka Street of Kambang Iwak,